Association of Menstrual Disorders with Body Mass Index in Undergraduate Medical Students - Rizvi, Shabnam; Khatoon, Fareha; Ahmad, Ayesha; Khan, Kashish Ayaz; Ekta, -; Singh, Kajal (International Journal of Human and Health Sciences (IJHHS), 2021)
Objective: Menstrual disorders constitute one of the major problems faced by medical students globally. Amongst the various factors attributed as causative factors in menstrual cycle variations, include body mass index [BMI] is the most easily modifiable factor. As we still do not have clear answers, this study was planned to study the association of menstrual disorders with BMI. Methodology: This is a cross sectional study, done in undergraduate female medical students in the age group of 18 to 30 years. Exclusion criteria included pregnancy, breast feeding, <12 months post-partum, <6 months post abortion/miscarriage, concomitant medical disorders and intake of hormonal medication. Data was collected for socio-demographic variables, detailed menstrual history, obstetric and medical history. Examination recorded anthropometric details, hirsutism, acne, any signs of virilization. Menstrual cycle variables were studied for their association with BMI. Results: A total of 254 students participated in the study with an average age of 23.9 years. Dysmenorrhea was globally found. Majority of cases were mild dysmenorrhea. Premenstrual syndrome [PMS] was seen commonly, commonest symptoms being mood swings and abdominal cramps. There was no association between mean menstrual blood loss [MBL], PMS and BMI and poor association with dysmenorrhea. Conclusion: Dysmenorrhea and PMS were very commonly seen and were not related to BMI. The mean MBL was independent of BMI. A rise in BMI had a positive association with cycle irregularity. International Journal of Human and Health Sciences Vol. 05 No. 03 July’21 Page: 330-335